PERAN PEMERINTAH KOTA MALANG DALAM MENINGKATKAN KESIAPSIAGAAN MASYARAKAT MENGHADAPI BENCANA (STUDI MANAJEMEN BENCANA) - Rusli, Rusli; 'Ulya, Ayu Fitriatul (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2018)
In Indonesia, the dangers of disasters such as floods, droughts, storms, and landslides have caused much loss of human lives and livelihoods, economic and infrastructure degradation, social order changes as well as environmental damage. In the face of disasters, the improvement of the system's preparedness in the community to reduce the risk of hazards is done through mitigation and adaptation efforts. Under Law No.26 of 2007 on spatial planning confirms disaster mitigation to be an important aspect of attention. Malang city of East Java including the recorded area is potentially prone to disasters, either flood, landslides, tectonic earthquakes or volcanic earthquakes. This study aims to determine the efforts of Malang City Government to improve community preparedness in facing the threat of disaster in Malang. The method used is positivism approach with qualitative approach. The result of this research indicates that the readiness of Malang City Government in facing disaster is with structural and non-structural mitigation. The structural mitigation effort that is done is the improvement of urban drainage channels, increasing the RTH and RTNH, incessant in the greening program by building a city park where as a tourist place is also useful for urban RTH, river normalization, reforestation on the banks of the Brantas river and other small rivers and cutting big trees on the street. While the effort in non-structural mitigation is the existence of regional regulations governing disaster (Malang Regional Regulation No. 1 of 2017 on Disaster Management Implementation, Strategic Plan (RENSTRA) BPBD Malang City 2015 - 2018), build synergy program with all actors (ministries, state institutions, social organizations, business entities, and universities) to empower communities, simulate increased knowledge and community awareness, increase community capacity to reduce and adapt to disaster risks by simulating and direction.Keywords: disaster; preparedness; mitigation